A closeup look at pollination - Kagan, Norman; Forman, Gary; Science Screen Report ([s.l.] : Allegro Film Productions, 1980)
This programme surveys the various ways of plant pollination, involving air and water currents, insects and other animals and intricate methods involving traps, lures and decoys- all in amazing closeup.
Narrated in Bahasa Melayu; backup available in U-matic 3/4 in.
Copy available in DVD format
Keywords: Pollination